Pythagorean Identities

Mathematics
Tutor: None Selected Time limit: 1 Day

Prove that (tanθ - 1/cosθ)^2 = sinθ-1/sinθ+1


Feb 8th, 2015

(tanθ - 1/cosθ)^2 = tan^2 θ - 2 tanθ/cos θ + 1/cos^2 θ

= sin^2 θ / cos^2 θ - 2 sinθ/cosθ/cosθ + 1/cos^2 θ

= (sin^2 θ - 2sinθ + 1) / cos^2 θ

= (sinθ - 1)(sinθ - 1) / 1-sin^2 θ

= (sinθ - 1)(sinθ - 1) / (1+sinθ)(1-sinθ) = 1-sinθ/1+sinθ

Feb 8th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Feb 8th, 2015
...
Feb 8th, 2015
Dec 3rd, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer